The Utilization of Jamboard to Improve Students` Writing Skills in Personal Letter - Irmayani Irmayani; Lailatul Masruroh; Eka Cristin Wulandari (UNIB Press, 2022)
This study used pre-experimental research, conducting one group pre-test and post-test to examine the effectiveness of using Jamboard application media to improve students' writing skills. Furthermore, this study focused on common writing challenges that students face, such as using acceptable grammar, vocabulary, and mechanics when writing personal letters. Twenty-eight senior high school students majoring in Teknik Kendaraan Ringan were carefully chosen from SMK Abdurrahman Wahid Banjarmadu (TKR). The data revealed an improvement in the students' writing ability in personal letters utilizing jamboard by Wilcoxon signed rank test. According to the data, the positive learning outcomes for pre-test and post-test with a mean rank or average rise 14,50. While the number of sum of ranks is 406,00. Based on statistic value of Wilcoxon test the significance (2-tailed) < 0,05. It signifies that the alternative hypothesis (H1) was accepted because there was a substantial difference in the students' writing skills before and after treatment with Jamboard, whereas the null hypothesis (Ho) was denied. After examining the data, the researcher concluded that jamboard could be an alternate media for improving students' personal letter writing abilities. There are a total of 406,00 rankings. The Wilcoxon test has a significance threshold of 0.05 based on the statistic value (2-tailed). It signifies that the alternative hypothesis (H1) was accepted since there was a substantial difference in the students' writing ability before and after treatment with Jamboard, whereas the null hypothesis (Ho) was denied. Following an examination of the data, the researcher concluded that jamboard could be a viable alternative medium for boosting students' personal letter writing talents.